Tunable Two-Section InAs/InP Quantum-Dash Laser: Numerical Modeling and Analysis - Mohammed Zahed Mustafa Khan (IEEE Photonics Journal, 2018)
We report a multi-population rate-equation based numerical model for investigating broadband two-section InAs/InP quantum-dash laser. The model incorporates the quantum-wire-like nature of dashes along with the inhomogeneous broadening of the active region. Numerical results of light power–injection current and spectral characteristics at various absorber section lengths are shown to be in good agreement with the experimental results. Moreover, inhomogeneous broadening displayed a pivotal role in achieving large tunability from the monolithic two-section devices, in addition to demonstrating an extended lasing bandwidth. A blue-shift tuning window of 41.7 nm and bandwidth improvement of 18.5 nm is exhibited by 1000 μm cavity length device with largest active region inhomogeneity. In general, shorter 800–1000 μm and longer 2000 μm cavity length devices showed large wavelength tunability of 49 and 65 nm, respectively, in 1560–1640 nm wavelength region. This comprehensive analysis would enable design optimization of the tunable two-section devices that are considered potential key components in optical access networks.